2014
DOI: 10.4028/www.scientific.net/amr.896.626
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue and Mechanical Properties of Aluminium-Copper Bi-Metal Tubes

Abstract: Metallurgical bonded aluminium-copper bi-metal tube has a future prospect as an alternative material to copper in the heat, ventilation and air-conditioning (HVAC) industries. The application of aluminum-copper bi-metallic material is seems practical in maintaining the quality of existing products. However, the mechanical strength and fatigue properties of the bi-metal tubes are unknown. In this study, metallurgical, mechanical and fatigue properties of the copper phosphorous alloy and aluminium-copper bi-meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…It provides a reliable basis for the fatigue failure analysis of 9 Cr 1 Mo steel tubes for boilers. Sajuri et al [19] characterized the metallurgical, mechanical, and fatigue properties of copper-phosphorus alloys and aluminum-copper bimetallic tubes by metallographic analysis and tensile, bending, and fatigue tests. The results showed that a fragile Al-Cu intermetallic compound was found in the transition layer between Al and Cu.…”
Section: Of 14mentioning
confidence: 99%
“…It provides a reliable basis for the fatigue failure analysis of 9 Cr 1 Mo steel tubes for boilers. Sajuri et al [19] characterized the metallurgical, mechanical, and fatigue properties of copper-phosphorus alloys and aluminum-copper bimetallic tubes by metallographic analysis and tensile, bending, and fatigue tests. The results showed that a fragile Al-Cu intermetallic compound was found in the transition layer between Al and Cu.…”
Section: Of 14mentioning
confidence: 99%
“…Finally, through fracture morphology analysis, it was found that the leakage in a titanium tube was caused by fatigue. Sajuri et al [26] studied the mechanical strength and fatigue properties of bimetallic pipes with an experimental method. The experimental results showed that the fatigue strength of aluminum copper bimetallic tube was about half lower than that of copper alloy tube.…”
Section: Introductionmentioning
confidence: 99%
“…Copper (Cu) and aluminium (Al) metallic alloys have broad applications in heating, ventilation and air conditioning, refrigeration and electrical industries due to their properties, such as high electrical and thermal conductivity and corrosion resistance [1][2][3][4]. Cu alloy is a relatively expensive material with a higher density compared with Al alloy [5].…”
Section: Introductionmentioning
confidence: 99%